(untitled) (Bioagro, 2020)
The Asian citrus psylid, Diaphorina citri (Hemiptera: Liviidae), is a new pest in Ecuador detected in 2013. Its importance lies in the fact that it is a vector of the bacterium Candidatus Liberibacter which causes huanglongbing, a devastating disease in citrus. During October 2016 - March 2017 its biological cycle, survival, fertility and population statistics (Ro: net reproductive rate, Tg: generational time, and rm: intrinsic rate of population development) were studied under laboratory conditions. On its host, Murraya paniculata, two treatments were compared: T1, bare root plants in water, and T2, plants on soil as a substrate. The Wilcoxon test was used for comparisons. The biological cycle showed differences (P≤0.05) between treatments, with an amplitude of 16.0 to 16.7 days. The rest of the variables showed no differences (P>0.05) between both treatments. The adult longevity was 25.0 and 25.7 days for females and 13.3 and 12.8 days, for males on T1 and T2, respectively. The survival curve was type I in both cases. Fertility was 780 eggs for T1 and 816.3 for T2. The Ro resulted in 3.9 times for individuals raised on T1 and 4.1 for those raised on T2. The Tg was approximately 26-27 days. Likewise, the rm was 0.05 for both treatments. The results show the short biological cycle of the insect and its biotic potential on both rearing conditions, which suggests that as a methodological alternative, laboratory biology studies of these insects can be performed on bare rooted plants on water.